An Opinion of Risk and Actuary Accounting in Insurance and Social Welfare - Cholakov, Nikola (Research Papers, 2007)
There is a particular interest during the last couple of years in risk models used in financial organizations and insurance companies aimed at clarifying the common theoretical and methodological principles and pursuing better transparency and reliability in risk assessment, forecasting and management.In this connection the European Union, following the European Commission initiative, is developing the Solvency II Project on risk problems and solvency of insurance companies targeted at better protection of the interest of insured through development of a modern regulatory framework and achieving higher capital adequacy and stability of the insurance sector.In this study the nature of risk is examined from actuarial point of view focusing on the mechanism of insurance and reinsurance, basic approaches, methods and models for risk assessment and forecasting, the transition from net premiums to gross premiums and the insurance tariffs, the accumulation of insurer's risk, the nature of safety loading and the reason for the insurance reserves and in this relation the mostly used risk models.Some comparisons are made with the social security to show how the latter corresponds to the theoretical and methodological principles of insurance in pursuing the final goal - security.